Naltriben promotes tumor growth by activating the TRPM7-mediated development of the anti-inflammatory M2 phenotype - Viviane Nascimento Da Conceicao; Yuyang Sun; Manigandan Venkatesan; Jorge De La Chapa; Karthik Ramachandran; Rahul S. Jasrotia; Victor Drel; Xiufang Chai; Bibhuti B. Mishra; Muniswamy Madesh; Brij B. Singh (npj Precision Oncology)
Abstract Macrophage plasticity is critical for maintaining immune function and developing solid tumors; however, the macrophage polarization mechanism remains incompletely understood. Our findings reveal that Mg2+ entry through distinct plasma membrane channels is critical to macrophage plasticity. Naïve macrophages displayed a previously unidentified Mg2+ dependent current, and TRPM7-like activity, which modulates its survival. Significantly, in M1 macrophages, Mg2+ entry is facilitated by a novel Mg²-dependent current that relies on extracellular Mg2+, which was crucial for activating iNOS/NFκB pathways and cellular bioenergetics, which drives pro-inflammatory cytokines. Conversely, in M2 macrophages, Mg2+ entry occurs primarily through TRPM7 channels, pivotal for IL-4 and IL-10-mediated anti-inflammatory cytokine secretion. Notably, the Mg2+ deficient diet or addition of TRPM7 agonist Naltriben suppresses the M1 phenotype while promoting angiogenic factors and fostering tumor growth. These findings suggest that Mg2+ flux via specific channels is indispensable for macrophage polarization, with its dysregulation playing a pivotal role in tumor progression.